The Role of Protein SUMOylation in Human Hepatocellular Carcinoma: A Potential Target of New Drug Discovery and Development - Hongchao Yuan (MDPI AG, 2021)
Small ubiquitin-like modifier (SUMO) is a highly conserved post-translational modification protein, mainly found in eukaryotes. They are widely expressed in different tissues, including the liver. As an essential post-translational modification, SUMOylation is involved in many necessary regulations in cells. It plays a vital role in DNA repair, transcription regulation, protein stability and cell cycle progression. Increasing shreds of evidence show that SUMOylation is closely related to Hepatocellular carcinoma (HCC). The high expression of SUMOs in the inflammatory hepatic tissue may lead to the carcinogenesis of HCC. At the same time, SUMOs will upregulate the proliferation and survival of HCC, migration, invasion and metastasis of HCC, tumour microenvironment as well as drug resistance. This study reviewed the role of SUMOylation in liver cancer. In addition, it also discussed natural compounds that modulate SUMO and target SUMO drugs in clinical trials. Considering the critical role of SUMO protein in the occurrence of HCC, the drug regulation of SUMOylation may become a potential target for treatment, prognostic monitoring and adjuvant chemotherapy of HCC.